Circulating hsa-miR-323b-3p in Huntington's Disease: A Pilot Study - Ferraldeschi, Michela; Romano, Silvia; Giglio, Simona; Romano, Carmela; Morena, Emanuele; Mechelli, Rosella; Annibali, Viviana; Ubaldi, Martina; Buscarinu, Maria Chiara; Umeton, Renato; Sani, Gabriele; Vecchione, Andrea; et al. (Frontiers in Neurology, 2021)
The momentum of gene therapy in Huntington disease (HD) deserves biomarkers from easily accessible fluid. We planned a study to verify whether plasma miRNome may provide useful peripheral “reporter(s)” for the management of HD patients. We performed an exploratory microarray study of whole non-coding RNA profiles in plasma from 9 patients with Huntington disease (HD) and 13 matched controls (8 healthy subjects – HS - and 5 psychiatric patients – PP - to minimize possible iatrogenic impact on the profile of non-coding RNAs). We found an HD-specific signature: down-regulation of hsa-miR-98 (fold change -1.5, p 0,0338 HD vs HS, and fold change - 1,5, p 0,0045 HD vs PP) and up-regulation of hsa-miR-323b-3p (fold change 1,5, p 0,0007 HD vs HS, and fold changes 1,5, p 0,0111 HD vs PP). To validate this result in an independent cohort, we quantify by digital droplet PCR (ddPCR) the presence of the two microRNA in the plasma of 33 HD patients, and 49 matched controls (25 HS and 24 PP patients). We were able to confirm that hsa-miR-323b-3p was up-regulated in HD and pre-manifest HD vs HS and PP: the median values (1st- 3rd quartile) were 4.1 (0.9-10.53) and 5.8 (1.9-10.70) vs 0.69 (0.3-2.75) and 1.4 (0.78-2.70) respectively; p<0.05. No significant difference was found for hsa-miR-98. The potential of hsa-miR-323b-3p to distinguish HD group and controls was investigated using ddPCR values in a ROC curve analysis: hsa-miR-323b-3p showed good accuracy in detecting HD, with an area under the curve of 0.759 (CI 0.627-0.892 p=0.001). To evaluate the biological plausibility of the hsa-miR-323b-3p as a component of the disease pathophysiology, we performed a bioinformatic analysis based on its targetome and the huntingtin (HTT) interactome. We found a statistically significant over-connectivity between the targetome of hsa-miR-323b-3p and the HTT interactome (p=1.48e-08). Furthermore, there was a significant transcription regulation of the HTT interactome by the miR-323b-3p targetome (p=0.02). The availability of handy, reproducible, and minimally invasive biomarkers coming from peripheral miRNome may be valuable to characterize the illness progression, to indicate new therapeutic targets, and to monitor the effect of disease-modifying treatments.